A review of mode I dominant interfacial fracture toughness test methods of skin-core bonding for thermoplastic composite sandwich structures. (June 2023) - Weidmann, Felix; Ziegmann, Gerhard; Wieser, Jürgen
Increased lightweight design via composite sandwich structures is a promising approach due to their exceptionally high weight-specific mechanical properties. The involved high cost when using sandwich composite structures has hindered applications in cost-sensitive markets up to now. However, full thermoplastic composite sandwich structures enable a cost reduction using novel processing routes based on fusion bonding of core and facesheet. In order to optimize such full thermoplastic composite sandwich structures and to ensure proper bonding of facesheet and core after manufacture, valid test methods for the quantification of skin-core interfacial bonding are required. This paper reviews existing test methods for the determination of Mode I dominant interfacial fracture toughness of sandwich structures. The main focus is set on cantilever beam tests as well as on peel tests. Based on a definition of requirements for suitable test methods, their applicability for full thermoplastic composite sandwich structures is evaluated. The Mandrel Peel Test results as most promising test method for thermoplastic sandwich structures, especially with thin facesheets.